2023
DOI: 10.1021/acsenergylett.3c01802
|View full text |Cite
|
Sign up to set email alerts
|

Concentrated Chlorine-Based Electrolyte Enabling Reversible Cl3/Cl Redox for Energy-Dense and Durable Aqueous Batteries

Bo Wen,
Cheng Yang,
Jing Wu
et al.

Abstract: Redox of chlorine with high potential and specific capacity has attracted wide attention for energy storage applications, while it suffers from an undesired disproportionation reaction in aqueous electrolytes which hinders its development. Herein we propose a strategy via a unique solubilization effect of metal-halide complex ions to construct a high concentration of chloride (over 30 m) electrolyte with low cost to stabilize the oxidation products and suppress the side reactions, thus representing a high reve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…After charging, a broad peak appeared at ∼270 nm by the electrolyte, which is very likely indicative of the [Cl 3 ] − anion. 51,52 To further confirm the existence of the polychloride monoanions formed with the Mn 3 O 4 structure after charging in the 20 M ZnCl 2 + 5 M NH 4 Cl WiSE, we immersed the fully charged Mn 3 O 4 electrode in an aqueous solution of 0.5 M KI. It was observed that the color of the KI solution quickly turned brownish, thereby indicating the presence of the polychloride monoanions as the charge products with the Mn 3 O 4 host (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…After charging, a broad peak appeared at ∼270 nm by the electrolyte, which is very likely indicative of the [Cl 3 ] − anion. 51,52 To further confirm the existence of the polychloride monoanions formed with the Mn 3 O 4 structure after charging in the 20 M ZnCl 2 + 5 M NH 4 Cl WiSE, we immersed the fully charged Mn 3 O 4 electrode in an aqueous solution of 0.5 M KI. It was observed that the color of the KI solution quickly turned brownish, thereby indicating the presence of the polychloride monoanions as the charge products with the Mn 3 O 4 host (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Aer charging, a broad peak appeared at ∼270 nm by the electrolyte, which is very likely indicative of the [Cl 3 ] − anion. 51,52 To further…”
Section: Characterization Of the Operation Of Thementioning
confidence: 99%